What It Feels Like : Visceral Rhetoric and the Politics of Rape Culture - Larson, Stephanie R. (Stephanie Rae), 1989- (Book collections on Project MUSE., 2021)
"Investigates contemporary and historical rhetorics of rape culture within institutional, legal, cultural, and medical discourses. Examines how discourses about rape rely on strategies of containment and deny the felt experiences of victims, ultimately stalling broader claims for justice in the United States"--